(untitled) (Progressive Agriculture, 2016)
Orange is one of the most import fruit crops that generate additional cash income for market actors. The study was investigated the marketing system of orange , value addition, roles and functions of value chain actors with the help of primary data collected from both farmers (forty) through simple random sampling and value chain actors (thirty) through purposive sampling by using structured questionnaire and face to face interview technique. The gross return and net return of farmers were estimated Tk. 2, 70,000 and Tk. 22084.77 per hectare respectively. Per quintal value addition of orange of bepari, aratdar, wholesaler and retailer were estimated at Tk. 800, Tk. 340, Tk. 700 and Tk. 1000 respectively. The net marketing margin per quintal of orange of bepari, aratdar, wholesaler and retailer were estimated at Tk. 293.59, Tk. 107.32, Tk. 356.46 and Tk. 700.8 respectively. Among the different actors, retailer incurred highest (in percentage) value addition and net marketing margin. On the other hand, aratdar incurred lowest marketing cost and marketing margin and bepari incurred highest (in percentage) marketing cost but adding second highest value in compare to another. Progressive Agriculture 27 (3): 327-338, 2016